2018
DOI: 10.1002/bse.2232
|View full text |Cite
|
Sign up to set email alerts
|

Innovation intensity, creativity enhancement, and eco‐innovation strategy: The roles of customer demand and environmental regulation

Abstract: This study develops a contingency framework to investigate how and when innovation intensity and creativity enhancement affect a firm's eco-innovation strategy by drawing upon the perspectives of the resource-based view and stakeholder theory.This investigation aims to explore whether firms with high innovation intensity and creativity enhancement really pursue eco-innovation strategy. Our examination is based on a sample of 2,126 manufacturing firms. By using a hierarchical regression, the results reveal that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
77
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 73 publications
4
77
2
Order By: Relevance
“…Recent studies have started to explore the contextual role of stakeholder pressure in the green knowledge sharing–green innovation link. However, the results diverge largely from one another, revealing a positive effect (Liao & Tsai, ; Tsai & Liao, ) or no effect (Zhu & Zhu & Sarkis, ). The mixed results indicate that even at high levels of stakeholder pressure, green knowledge sharing may not directly contribute to green innovation, suggesting a possible missing link.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…Recent studies have started to explore the contextual role of stakeholder pressure in the green knowledge sharing–green innovation link. However, the results diverge largely from one another, revealing a positive effect (Liao & Tsai, ; Tsai & Liao, ) or no effect (Zhu & Zhu & Sarkis, ). The mixed results indicate that even at high levels of stakeholder pressure, green knowledge sharing may not directly contribute to green innovation, suggesting a possible missing link.…”
Section: Introductionmentioning
confidence: 88%
“…However, some researchers have found that knowledge sharing provides only opportunities to improve green innovation (Chen et al, ; Gebauer et al, ), as the entirely new green knowledge shared from other firms is not necessary to be compatible with a firm's existing knowledge (Wong, ). Although recent studies have started to explore various contingencies of the green knowledge sharing‐green innovation link, for example, knowledge characteristics (Chavez et al, ), environmental turbulence (Song & Yang, ), and institutional pressure (Liao & Tsai, ), limited research has explicitly incorporated the mediation mechanism and investigated the boundary conditions for such a mechanism. We thus explore, for the first time, the mediating mechanism through which a firm can realize the green innovation benefits of green knowledge sharing and the conditions under which this mechanism may work.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Current research suggests that factors, such as institutional pressures (Lin & Ho, ), environmental regulation (Hojnik & Ruzzier, ; You, Zhang, & Yuan, ; Zhang, Wang, Xue, & Yang, ), stakeholder pressure (Kawai, Strange, & Zucchella, ), external knowledge resources (Arfi, Hikkerova, & Sahut, ; Laursen & Salter, ), big data and environmental ethics (El‐Kassar & Singh, ), and market demands (Mondéjar‐Jiménez, Segarra‐Oña, Peiró‐Signes, Payá‐Martínez, & Sáez‐Martínez, ), influence firms' green innovation. As a complex and costly technological frontier (De Marchi, ; Liao, ), green innovation requires more diversified knowledge resources than traditional innovations (Cainelli, De Marchi, & Grandinetti, ; Martínez‐Ros & Kunapatarawong, ; Pacheco, Alves, & Liboni, ), especially complex technological knowledge and skills for eliminating environmental pollution (Liao & Tsai, ). However, due to insufficient internal knowledge resources, firms have to search for external knowledge to conduct green innovation (Du et al, ).…”
Section: Introductionmentioning
confidence: 99%